2024
DOI: 10.1039/d3ta07380g
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-doped cobalt molybdenum oxide with a hydrangea-like structure for bi-functionally efficient overall water splitting

Jie Dong,
Saiyi Chen,
Cuncai Lv
et al.

Abstract: Developing an efficient bi-functional water-splitting catalyst is crucial for advancing sustainable hydrogen energy applications. A novel sulfur-doped cobalt molybdenum oxide (S-CoMoO) catalyst with a hydrangea-like structure was synthesized in situ...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
0
0
Order By: Relevance
“…Oxygen vacancies and mesoporosity are crucial for its excellent HER performance. Dong et al 9 reported that a hydrothermal process synthesized sulfur-doped cobalt molybdenum oxide. Such an electrocatalyst showed improved electrocatalytic performance owing to the modified composition and morphology.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Oxygen vacancies and mesoporosity are crucial for its excellent HER performance. Dong et al 9 reported that a hydrothermal process synthesized sulfur-doped cobalt molybdenum oxide. Such an electrocatalyst showed improved electrocatalytic performance owing to the modified composition and morphology.…”
Section: ■ Introductionmentioning
confidence: 99%